Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM64 - Dagmar Kieke; Christian dos Santos Ferreira; Laura Frahm; Andrea Gerriets; Asmund Herland; Gard Stokland (PANGAEA, 2022)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg EM 122 multibeam echosounder was not continuously recorded during RV MARIA S. MERIAN cruise MSM64. Data was recorded on 2 days between 2017-05-30 and 2017-05-31 to re-calibrate the system. This dataset contains a survey west of the coast of Ireland. The approximate average depth of the entire dataset is around 2900m. 43 additional sound velocity profiles derived were generated on board, however no multibeam echosounder data were acquired in the vicinity of these events. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus SVP files are added to this dataset. However, also data analysis of the multibeam raw data revealed that SVP has been changed during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather good since the gridded hillshade data showed relatively few obstacles. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).